Enhanced Photocatalytic Activity and Magnetic Properties of CoFe2O4/TiO2-Ag/S for Visible Light-Driven Photodegradation of Methylene Blue - Kunarti, Eko Sri; Agustiningsih, Dewi; Pambudi, Fajar Inggit; Syoufian, Akhmad; Santosa, Sri Juari (Universitas Gadjah Mada, 2025)
Environmental concerns drive the need for effective photocatalysts that can operate under visible light to degrade organic pollutants in wastewater. This study investigated TiO2-based photocatalyst doped with Ag and S to enhance its visible-light response, modified further with CoFe2O4 to introduce magnetic properties, resulting in a composite, CoFe2O4/TiO2-Ag/S. The synthesis was carried out by using cobalt nitrate hexahydrate and ferric nitrate nonahydrate for CoFe2O4 precursor, titanium tetraisopropoxide for TiO2 precursor, and silver nitrate with thiourea for Ag and S dopants. Results from characterization analyses, including FTIR, XRD, UV-vis, SEM-EDX, TEM, and VSM, confirmed the composite structure, with magnetic properties reflected in saturation magnetization of 10.69 emu g−1 and an extended UV-vis absorption edge indicating improved visible light activity. Photocatalytic tests for methylene blue degradation showed the highest performance (92%) with a 1:1 Ag:S ratio under visible light at pH 10 over 120 min, using 20 mg of catalyst in 5 ppm solution. Additionally, the composite demonstrated strong stability, retaining efficiency across six cycles of reuse.